A PROMISING DNA GROOVE BINDER AND PHOTOCLEAVER BASED ON A DINUCLEAR RUTHENIUM(II) COMPLEX - Ya-xuan Mi; Shuang Wang; Xue-Xue Xu; Hua-Qian Zhao; Ze-Bao Zheng; Xiao-Long Zhao (Journal of the Chilean Chemical Society, 2019)
A dinuclear ruthenium complex [Ru2(bpy)4(bip-phenol)](ClO4)4 {bpy = 2,2′-bipyridine, bip-phenol = 2,4-bis(1H-imidazo[4,5-f][1,10]phenanthrolin-2-yl) phenol} has been synthesized and characterized. The calf thymus (ct) DNA binding properties of the complex are investigated by means of DNA viscosity and optical spectroscopic techniques of UV-visible absorption and emission spectral titrations, steady-state emission quenching with ferrocyanide, ethidium bromide competitive binding, DNA thermal denaturation and reverse salt effect, together with molecular simulation technology. The results suggest that the complex is a promising DNA groove binder with a large DNA binding constant on 106 M−1 order of magnitude. The fluorescence of the complex manifests by 6.3-fold upon binding saturately to DNA. The complex is also demonstrated to be an efficient photocleaver of pBR 322 DNA.